Manners - "Jamieson,Alison" (Wayland Hove, 1993)
The book Terrorism by Alison Jamieson offers a comprehensive overview of the phenomenon of terrorism, providing historical context and examining various case studies, with a particular focus on regions such as the Middle East and Northern Ireland. Jamieson delves into the motivations behind terrorist activities, the methods employed, and the broader political and social implications. This work serves as an informative resource for understanding the complexities of terrorism and its impact on global affairs.